2013
DOI: 10.1128/jcm.00809-13
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Bacterial Pathogens in Patients Presenting with Gastroenteritis by Use of the EntericBio Real-Time Gastro Panel I Assay

Abstract: bIn this study, we evaluated the use of EntericBio real-time Gastro Panel I (Serosep, Limerick, Ireland) for routine use in a clinical microbiology laboratory for simultaneous detection of Campylobacter jejuni, coli, and lari, Shiga toxin-producing Escherichia coli (STEC), Salmonella spp., and Shigella spp. in feces. This system differs from its predecessor (the EntericBio Panel II system, Serosep) in that it allows real-time detection of pathogens directly from feces, without pre-enrichment. It also specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…This is in line with results from Portugal, where Campylobacter species were detected in 31.9% of diarrheic fecal samples, with C. jejuni and C. concisus being the most prevalent species (13.7% and 8.0%, respectively) (56). Furthermore, based on PCR analysis, the prevalences of C. ureolyticus in gastroenteritis cases in Ireland in the period from 2009 to 2012 ranged from 1.15 to 1.30% (57,58). Furthermore, molecular screening for seven members of the Campylobacter genus by using PCR revealed the overall prevalence of Campylobacter species in patients with gastroenteritis from southern Ireland to be 4.7%, with C. jejuni being the predominant species, accounting for 66% of all Campylobacter species detected, followed by C. ureolyticus (22.3% of all Campylobacter species detected), C. coli (6.7%), C. fetus (2.1%), C. hyointestinalis (1.3%), C. upsaliensis (1.1%), and C. lari (0.5%) (59 (61).…”
Section: Epidemiologysupporting
confidence: 72%
See 1 more Smart Citation
“…This is in line with results from Portugal, where Campylobacter species were detected in 31.9% of diarrheic fecal samples, with C. jejuni and C. concisus being the most prevalent species (13.7% and 8.0%, respectively) (56). Furthermore, based on PCR analysis, the prevalences of C. ureolyticus in gastroenteritis cases in Ireland in the period from 2009 to 2012 ranged from 1.15 to 1.30% (57,58). Furthermore, molecular screening for seven members of the Campylobacter genus by using PCR revealed the overall prevalence of Campylobacter species in patients with gastroenteritis from southern Ireland to be 4.7%, with C. jejuni being the predominant species, accounting for 66% of all Campylobacter species detected, followed by C. ureolyticus (22.3% of all Campylobacter species detected), C. coli (6.7%), C. fetus (2.1%), C. hyointestinalis (1.3%), C. upsaliensis (1.1%), and C. lari (0.5%) (59 (61).…”
Section: Epidemiologysupporting
confidence: 72%
“…A recent study by Granato and colleagues compared three commercially available kits with culture-based techniques and found that the three immunoassays had sensitivities that ranged from 98.5 to 99.3% and specificities that ranged from 98.0 to 98.2%, while standard culture had a sensitivity of 94.1% (275). Furthermore, a number of real-time assays are also available for the detection of Campylobacter species, some of which are capable of detecting more than one species at a time, including C. jejuni, C. coli, and C. lari (57). Interestingly, Javed and colleagues also described an assay to detect C. jejuni and C. coli based on the ability of recombinant receptor binding proteins from the C. jejuni bacteriophage NCTC12673 to agglutinate in the presence of these species (276).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…7 Since we did not perform confirmatory molecular testing for this target, the significance of these results remains uncertain. EIEC is thought to be uncommon in high-income countries, but few epidemiological studies have been undertaken because of shared phenotypic and genetic characteristics with Shigella and non-enteropathogenic E. coli.…”
Section: Discussionmentioning
confidence: 96%
“…3 Three studies have been published to date on the performance of EntericBio assays. 2,7,10 Two of these compared the performance of different versions of the same assay, and did not address Salmonella sensitivity versus culture. O'Leary et al 2 tested only four of 773 samples positive by culture for Salmonella, insufficient to identify performance issues for this target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation